The effect of green product and green promotion on increased consumer loyalty at starbucks coffee - erina subiantoro; Lexi Pranata Budidharmanto (Institut Pariwisata dan Bisnis Internasional, 2021)
Increasing public awareness of the environment has made companies implement green product and green promotion strategies to increase consumer loyalty. So, the purpose of this study was to determine the influence between green product and green promotion on consumer loyalty at Starbucks Coffee. This study used a sample of 203 respondents who were processed by multiple linear regression. The results showed that the green product and green promotion partially had a positive and significant effect on consumer loyalty. Green products have the biggest influence on consumer loyalty. This shows that green products have an important role in increasing consumer loyalty at Starbucks Coffee. Also the green promotion can increase the consumer loyalty too.